Lumbosakral ve Spinopelvik İstabiliteye Neden Olan Av Tüfeği Yaralanması: Olgu Sunumu - (:unkn) unknown (My University, 2015)
Lumbosakral ve spinopelvik instabiliteye neden olan yaralanmalar nadir olup genellikle yüksekten düşme, trafik kazaları gibi yaralanmalar sonucu olup ateşli silah yaralanmaları sonrası nadir görülürler. Av tüfeği ile yakın atış sonrası L5, sakrum ve iliak kanatların parçalı kırığı sonucu lumbosakral ve spinopelvik instabiliteye neden olan, nadir görülen bir olguyu sunduk

Injuries which result in lumbosacral and spinopelvic instability are rare and usually occur generally as a result of falling from height, traffic accidents; however, they are rarely observed after gunshot injuries. We present a rare-seen case which took place after a close-shot with a shotgun and resulted in lumbosacral and spinopelvic instability as a result of fractures in L5, sacrum and iliac wing
Lumbosacral and Spinopelvic Instability As aResult of Shotgun Injury:Case Repot
Keywords: Tıbbi Araştırmalar Deneysel